Single-step, electrophoretically deposited hydroxyapatite/poly(vinyl alcohol)/chitosan/gentamicin coating for biomedical applications - Nevena Jaćimović; Marija Djošić; Ana Jankovic; Svetlana Grujić; Ivana Matić Bujagić; Jovica Stojanović; Maja Vukašinović-Sekulić; Vesna Kojić; Vesna Mišković-Stanković (Macedonian Journal of Chemistry and Chemical Engineering, 2023)
Biocomposite hydroxyapatite/poly(vinyl alcohol)/chitosan/gentamicin coatings were fabricated on titanium by electrophoretic deposition process (EPD) from an aqueous suspension using the constant voltage method.  Characterization of the deposited coatings was performed by scanning electron microscopy with field emission (FE–SEM), Fourier transform infrared spectroscopy (FT–IR) and X-ray diffraction (XRD) after immersion in simulated body fluid (SBF) at 37 °C. The concentration of the released gentamicin was determined using a high-performance liquid chromatography (HPLC) coupled with a mass spectrometer (MS). The release profile confirmed an initial “burst-release effect” with ~ 30% of gentamicin released in the first 48 h, which could be of assistance in the prevention of biofilm formation. Antibacterial activity was proven by the agar diffusion method on Staphylococcus aureus TL and Escherichia coli ATCC 25922 bacterial strains. Cytotoxicity was tested by the dye exclusion test (DET) on MRC-5 and L929 fibroblast cell lines, with both coatings expressing nontoxicity. The results showed the high applicability potential of a  poly(vinyl alcohol)-based biocomposite coating for medical purposes.